(untitled) (Journal of the College of Basic Education, 2022)
Education represents two main pillars of its great role in a society with development and education and education by elevation, as the educational and educational process occupies the interest of many thinkers, intellectuals, and workers in various educational fields in countries of the world, because of the progress and development of society and the interest in education as it varies in the level of career creativity among teachers. This is shown by the fluctuating level of participation of students within the lesson or external activities, between excellence and weakness in most of the participants, and here the research problem arises in the lack of appreciation of career creativity among teachers. The aim of the research was to identify the level of functional creativity of teachers of physical education and sports sciences in the directorates of education in Baghdad. The research sample is represented by (280) supervisors. As for the most important conclusions, the job creativity scale was prepared with (26) paragraphs and distributed over (6) areas.